Effect of elevated progesterone levels the day before ovulation on pregnancy outcomes in natural cycles of frozen thawed embryo transfer. (2nd September 2022) - Wu, Di; Yu, Ting; Shi, Hao; Zhai, Jun
Abstract: Objective: We aimed to analyze whether elevated progesterone levels on the day before ovulation affected pregnancy outcomes in natural cycles of frozen thawed embryo transfer (NC-FET). Methods: A retrospective analysis was conducted in a public university hospital. Data on clinical pregnancy, live birth, ectopic pregnancy, and miscarriage rates were collected, along with other patient data. Patients were divided into two groups according to their progesterone levels the day before ovulation: the progesterone elevation (PE) group (progesterone level >1.0 ng/mL) and the normal progesterone (NP) group (progesterone level ≤1.0 ng/mL). We assessed the effect of elevated progesterone levels in NC-FET by performing multivariate logistic regression analysis. Results: Overall 1159 women with tubal factor infertility who underwent NC-FET were enrolled, including 666 women who received cleavage-stage embryo transfers and 493 women who received blastocyst embryo transfers. When two cleavage-stage embryos were transferred, the clinical pregnancy rate was significantly higher in the PE than in the NP group following NC-FET ( p <  .05). After correcting for various confounders, we found that elevated progesterone levels (adjusted odds ratio [OR]: 1.672; 95% confidence interval [CI]: 1.089–2.566, p  = .018) improved the clinical pregnancy rate following transfer of two cleavage-stage embryos but did not affect the pregnancy rate when blastocyst-stage embryos were transferred (adjusted OR: 0.856; 95% CI: 0.536–1.369; p  = .517). Conclusions: The results showed that in patients undergoing cleavage-stage NC-FET, progesterone levels >1.0 ng/mL improved the clinical pregnancy rates. However, the level of progesterone had no effect on the clinical pregnancy rate for patients undergoing blastocyst-stage NC-FET.